RANCANG BANGUN MOBIL AERO ANTI GRAVITASI BERBASIS MIKROKONTROLLER DSPIC30F - Setyaji, Eric (Elektrika, 2017)
The car continues to develop the technology for the sake of convenience for the user to get a car. Currently the cars already provide many services, including : features - features, the fuelefficient, environmentally friendly, and safety while driving. But comfort when driving on the road is still not perceived as bottlenecks that often occur. Cars are often stuck in traffic will experience a diecasting machine, because the machine lights up constantly - constantly in a state of standstill. Researchers of this problem offers solutions in the field of transport. Researchers create Design of Aero Anti-Gravity Car Microcontroller-based dsPIC30F . It was inspired from a means of transportation that can resist the force of gravity, among others : airplanes, helicopters, jets and rockets. So that the principle of work on the Anti-Gravity Car s is the aerodynamic system of microcontroller-based dsPIC30F. Keywords : Aero Anti-grvitasi Car, DSPIC30F.Aerodynamic